Public Area Interventions in Service of Crime Prevention - Žunić-Pavlović, Vesna; Kovačević-Lepojević, Marina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
Public area surveillance is grounded in situational crime prevention, one of the four main directions in crime prevention (Welsh and Farrington, 2009). Situational prevention is aimed to identify, manage and control factors involved with criminal behavior (Cornish, Clark, 2003). Indirectly, the prevention effect is materialised through the development of informal social control and environmental cohesion too. The aim of this paper is to review the preventive interventions applied in public places (squares, parks, public buildings, streets, schools, universities, public transport, etc.) and provide a detailed description of the individual intervention's effect on crime control. Interventions like CCTV, street lighting, security guards, place managers, and defensible space will be discussed; the main advantages and disadvantages will be stressed, too. Public area surveillance is grouped into three types of surveillance: formal surveillance, natural surveillance and place managers (Cornish, Clark, 2003). The review of the public spectrum intervention’s evaluation studies will be given in the second part of the paper. The effectiveness of the public area interventions will be discussed by different criteria based on the results of the evaluation studies. At the end, we will make the recommendations about the proper public area interventions and promotion of the evidence- based crime prevention approach.